Clinical management of behavioral insomnia of childhood - Vriend, Jennifer (Dove Medical Press, 2011)
Behavioral insomnia is highly prevalent, affecting approximately 25% of children. It involves difficulties initiating and maintaining sleep and frequently results in inadequate sleep, leading to an array of negative effects for both the child and the child’s family. In this paper, we describe a variety of empirically supported behavioral interventions for insomnia from infancy through adolescence. We explore how biological, cognitive, and psychosocial developmental changes contribute to behavioral insomnia and how these changes may affect sleep and behavioral interventions. We also discuss barriers that prevent families from accessing interventions, including why many empirically-supported behavioral interventions are overlooked by health care providers.